KEBIASAAN MAKAN DAN MAKANAN LABI - LABI (AMYDA CARTILAGINEA) DI SUNGAI BELAK DESA SEBADU KABUPATEN LANDAK KALIMANTAN BARAT - Triponia, Triponia; Soetignya, Widadi Padmarsari; Kurniadi, Bambang (Jurnal Sains Pertanian Equator, 2025)
Labi - labi (Amyda cartilaginea) is one of the soft-shelled freshwater turtle species that has been included in the vulnerable status by IUCN. The capture of labi - labi is done for consumption and sale without regard to its size, and is not balanced with cultivation efforts, it is feared that it can threaten the sustainability of labi - labi in natural habitats. This study aims to determine the eating habits and food of labi - labi which can later become scientific information for cultivation and conservation activities. This research was conducted during February - March 2025 in Belak River, Sebadu Village, Landak Regency, Kalimantan Province. Data taken in the form of total length, weight, capture time, and type of food. Analysis of eating habits and food of labi - labi was done using the stomach fullness index and the largest part index. The results of the analysis showed that the feeding habits of labi-labi in Belak River were actively foraging at night and their food habits were omnivorous with a food composition consisting of plants (50.53%), mollusca (33.09%), fish (16.20%) and worms (0.18%).